Beer-brewing powered by controlled hydrodynamic cavitation: Theory and real-scale experiments. (20th January 2017) - Albanese, Lorenzo; Ciriminna, Rosaria; Meneguzzo, Francesco; Pagliaro, Mario
Abstract: The basic beer-brewing industrial practices have barely changed over time. While well proven and stable, they have been refractory to substantial innovation. Technologies harnessing hydrodynamic cavitation have emerged since the 1990s' in different technical fields including the processing of liquid foods, bringing in advantages such as acceleration of extraction processes, disinfection and energy efficiency. Nevertheless, so far beer-brewing processes were not investigated. The impacts of controlled hydrodynamic cavitation, managed by means of a dedicated unit on a real microbrewery scale (230 L), on the beer-brewing processes is the subject of this paper. The physico-chemical features of the obtained products, analyzed by means of professional instruments, were compared with both literature data and data from the outcomes of a traditional equipment. Traditional processes such as dry milling of malts and wort boiling becoming entirely unnecessary, dramatic reduction of saccharification temperature, acceleration and increase of starch extraction efficiency, relevant energy saving, while retaining safety, reliability, scalability, virtually universal application to any brewing recipe, beer quality, were the most relevant experimental results. The impacts of these findings are potentially far reaching, beer being the worldwide most widely consumed alcoholic beverage, therefore highly relevant to health, environment, the economy and even to local identities. Graphical abstract: Highlights: First ever real-scale application of hydrodynamic cavitation to beer-brewing. Controlled hydrodynamic cavitation assisted brewing is safe, reliable, scalable. The application allows large savings of process time, energy and wash water. Traditional malts dry milling and wort boiling become unessential. Accelerated saccharification, starch extraction and utilization of hops α-acids.